Methodical instructions for laboratory works on topic "Design and development of relational databases using MySQL, implementation of business logic elements" - Kopp, Andrii Mykhailovych; Orlovskyi, Dmytro Leonidovych; Ved, Olena Valeriivna; Vasylenko, Artem Viktorovych (Національний технічний університет "Харківський політехнічний інститут", 2025)
In the framework of the laboratory practicum, students acquire the knowledge and skills necessary for: - Designing and developing relational databases using client-server database management systems (DBMS), with MySQL as an example; - Implementing business logic in the database based on stored procedures, functions, and triggers; - Ensuring data integrity; - Supporting data consistency and security based on transaction mechanisms and user rights. The goal of the laboratory practicum is to develop practical skills in students that are necessary for designing and developing databases (DB) when solving tasks related to the development, maintenance, and ensuring the quality ofsoftware.
Keywords: methodical instructions; laboratory works; relational databases design; relational database development; MySQL tools; business logic